ANALISIS KEMAMPUAN BERHITUNG SISWA DITINJAU DARI GENDER DI MADRASAH IBTIDAIYAH KABUPATEN SORONG - Aulia Pramudyani; Nasrul Fauzi; Muhammad Ramli (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2021)
This research is descriptive quantitative research. This research aims to analyze the level and differences in students' numeracy skills in terms of gender in Madrasah Ibtidaiyah, Sorong Regency. The subjects in this study were second-grade students of Madrasah Ibtidaiyah Sorong State, Madrasah Ibtidaiyah Muhammadiyah 2 Sorong Regency, and Madrasah Ibtidaiyah Al-Maarif 1 Sorong Regency, from 100 students obtained a sample of 80 students using the Solvin formula and technique disproportionate sample. The data collection technique in this study was a test with instruments in the form of test questions. Data analysis techniques using analysis descriptive and t-test, with prerequisite tests, namely normality test and homogeneity test. From the results of the analysis using the independent t-test, it was obtained sig value was. 0.960 > 0.05 so it is stated that H 0 is accepted and Ha is rejected. Based on the results show that; the numeracy level of male students is 73.90% male students and 74.15% female students in the high category with a difference of 0.25, and there is no significant difference between the ability to count students in terms of gender in Madrasah Ibtidaiyah Sorong Regency. Thus, gender differences cannot determine students' numeracy skills Ibtidaiyah Madrasa. This research is descriptive quantitative research. This research aims to analyze the level and differences in students' numeracy skills in terms of gender in Madrasah Ibtidaiyah, Sorong Regency. The subjects in this study were second-grade students of Madrasah Ibtidaiyah Sorong State, Madrasah Ibtidaiyah Muhammadiyah 2 Sorong Regency, and Madrasah Ibtidaiyah Al-Maarif 1 Sorong Regency, from 100 students obtained a sample of 80 students using the Solvin formula and technique disproportionate sample. The data collection technique in this study was a test with instruments in the form of test questions. Data analysis techniques using analysis descriptive and t-test, with prerequisite tests, namely normality test and homogeneity test. From the results of the analysis using the independent t-test, it was obtained sig value was. 0.960 > 0.05 so it is stated that H 0 is accepted and Ha is rejected. Based on the results show that; the numeracy level of male students is 73.90% male students and 74.15% female students in the high category with a difference of 0.25, and there is no significant difference between the ability to count students in terms of gender in Madrasah Ibtidaiyah Sorong Regency. Thus, gender differences cannot determine students' numeracy skills Ibtidaiyah Madrasa.